1999
DOI: 10.1136/jech.53.12.782
|View full text |Cite
|
Sign up to set email alerts
|

East Ireland 1980-1994: epidemiology of neural tube defects

Abstract: Study objective-The objective of the study was to describe the epidemiology of neural tube defects (NTD) in the eastern region of Ireland using the EUROCAT register of congenital malformations. Design, setting and patients-EUROCAT registries monitor the prevalence of congenital anomalies in defined populations using multiple sources for case ascertainment. All cases of NTD on the Dublin EUROCAT register born between 1980 and 1994 were extracted and analysed. The crude birth prevalence rate for all NTD, spina b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
30
1
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 15 publications
8
30
1
1
Order By: Relevance
“…Others had reported 0.73 (Daoud et al, 1996), 0.78 (Golalipour et al, 2007;Stevenson et al, 2000) and 0.85 (Samson, 2003), or even a male predominance 1.07 (Wasant & Sathienkijkanchai, 2005). The predominance of female anencephalic births over males in our study is similar to that seen in other countries and likewise the slight female predominance in spina bifida births (McDonnell et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Others had reported 0.73 (Daoud et al, 1996), 0.78 (Golalipour et al, 2007;Stevenson et al, 2000) and 0.85 (Samson, 2003), or even a male predominance 1.07 (Wasant & Sathienkijkanchai, 2005). The predominance of female anencephalic births over males in our study is similar to that seen in other countries and likewise the slight female predominance in spina bifida births (McDonnell et al, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…The spina bifida to anencephalic ratio is similar to that reported by other workers (McDonnell et al, 1999). Our research was shown that more than half of mortality is a consequence of anencephaly (Eurocat Working Group, 1991).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…One of us reviewed 20 such reports in 1986 (Fraser et al, 1986). Seven additional studies appeared thereafter (Stoll et al, 1988;Abrate et al, 1990;Angerpointner et al, 1990;Castilla et al, 1990;Wu et al, 1991;Bound et al, 1998;McDonnell et al, 1999). Figure 1 presents the results, based again on month of conception.…”
Section: Introductionmentioning
confidence: 92%
“…Among these, the myelomeningocele (protrusion of the nervous tissue and its covering through a defect in the vertebrae and skin) represents by far the most common type, accounting for about 90% of spina bifida cases [1,2]. Its incidence is reported to range from 2 to 20 per 10,000 births according to different geographic areas, being higher in the United Kingdom (from 5.9 to 13.1 per 10,000 births) and Asia (10.6 per 10,000 births) and lower in the United States (from 3.1 per 10,000 births) and in the other European countries (from 2.0 to 10.5 per 10,000 births) [3,4,5,6,7]. The causes of spina bifida are multifactorial, including genetic predisposition, environmental factors and maternal conditions [8].…”
Section: Introductionmentioning
confidence: 99%